Dampak Pengangkutan Komoditas Batubara di Sepanjang Alur Sungai Terhadap Kondisi Sosial dan Ekonomi Masyarakat - Syahputra, Dicky; Mujanah, Siti; Halik, Abdul; Hwihanus, Hwihanus (Journal of Trends Economics and Accounting Research, 2025)
This study aims to analyze the impact of coal shipping activities on the social and economic conditions of communities in Berau Regency, East Kalimantan. The increasing intensity of coal maritime transport in this region follows the rapid growth of the export-oriented mining industry. However, this development not only contributes to the local economy but also triggers various social dynamics within coastal areas and communities along the shipping routes. This research adopts a qualitative approach through field research methods. Data were collected through in-depth interviews and direct observation of 40 respondents, consisting of coastal residents, fishermen, port workers, and local government officials. Eighteen respondents were fishermen, nine respondents were coastal community members, six respondents were port workers, and seven respondents were local government officials. The data were analyzed descriptively to examine the relationship between the intensity of shipping activities and changes in the socio-economic structure of local communities. The findings indicate that coal shipping activities have generated positive economic impacts, such as increased employment opportunities and income levels, but have also led to several social issues, including environmental degradation, land conflicts, and a decline in coastal community well-being. Therefore, sustainable maritime management policies are required to ensure that the economic benefits gained from coal shipping do not compromise social welfare and environmental preservation in Berau Regency.